Characteristics Of Students’ Mathematical Problem-Solving Strategies In Problem-Based Learning Through Polya’s Stages - Ulfa Yuliana; Stepan Tudu; Nursupiamin Nursupiamin; I Wayan Sudarsana (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
This study aimed to explore the characteristics of students’ mathematical problem-solving strategies in Problem-Based Learning through Polya’s stages in solving compound interest problems. This study employed a qualitative descriptive case study. The participants consisted of 35 Grade XI students at SMA Negeri 2 Tolitoli, Central Sulawesi. Data were collected through problem-solving tests, interviews, observations, and documentation. Three representative students from high-, moderate-, and low-level problem-solving characteristic profiles were selected purposively for in-depth analysis. Data were analyzed using Miles and Huberman’s interactive model. The findings showed that students demonstrated different strategy characteristics across Polya’s stages. At the understanding stage, students demonstrated complete identification, partial understanding, and misunderstanding strategies. During the planning stage, conceptual, procedural, and trial-and-error strategies emerged. At the implementation stage, students demonstrated systematic solution, procedural error, and inconsistent-step strategies, while at the reflective stage, students showed solution evaluation, partial verification, and no verification strategies. Students with high-level profiles tended to demonstrate coherent and interconnected strategy patterns, whereas students with low-level profiles demonstrated fragmented and inconsistent processes. The findings further indicated that students’ strategies developed as interconnected processes in which difficulties emerging at earlier stages influenced subsequent stages. Reflective activities were identified as the weakest component of students’ mathematical problem-solving processes. The findings contribute theoretically to understanding how students’ mathematical problem-solving strategies emerge and develop across Polya’s stages within Problem-Based Learning environments. Practically, the findings highlight the importance of strengthening reflective activities and supporting interconnected strategic thinking in mathematics learning